Polycrystalline iron-loaded porous charcoal aerogel catalyst as well as preparation method and application thereof

By using polycrystalline iron-loaded porous biochar aerogel catalyst in the catalyst, and using Fe-C bond to support polycrystalline iron nanoparticles to form a honeycomb pore structure, the problems of low efficiency and poor stress resistance of the existing catalyst are solved, and the problem of low efficiency and poor stress resistance is achieved. It has efficient catalytic ozone oxidation and degradation of organic pollutants.

CN119259047APending Publication Date: 2025-01-07WENZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411440770.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing catalysts are inefficient in the catalytic ozone oxidation process, making it difficult to effectively remove organic matter with complex structures, and the iron-based materials have poor stress resistance and cannot play a stable role in water.

Method used

Polycrystalline iron-loaded porous biochar aerogel catalyst is used. This catalyst supports polycrystalline iron nanoparticles on the surface of porous biochar through Fe-C bonds, forming a honeycomb pore network structure, improving the mechanical strength and structural stability of the catalyst. And improve catalytic efficiency through abundant pores and reactive sites.

Benefits of technology

It significantly improves the catalytic ozone oxidation efficiency, can stably adsorb and degrade organic pollutants in water, improves the degradation efficiency of organic matter such as antibiotics, and reduces the decomposition rate of ozone, achieving efficient electron transfer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259047A_ABST
    Figure CN119259047A_ABST
Patent Text Reader

Abstract

The invention discloses a polycrystalline iron-loaded porous charcoal aerogel catalyst as well as a preparation method and application thereof, and relates to the field of carbon catalyst preparation. The polycrystalline iron loaded porous biochar aerogel catalyst comprises a porous biochar matrix, polycrystalline iron nanoparticles are loaded on a biochar sheet layer through Fe-C bonds, and the whole internal structure of the porous biochar aerogel is of a honeycomb-shaped pore network structure; according to the preparation method of the catalyst disclosed by the invention, the iron-based material and the carbon-based material are cross-linked together by utilizing ion exchange of a cross-linking agent, and the catalyst is prepared through freeze drying and high-temperature calcination treatment. The aerogel provided by the invention has a rich pore structure, can adsorb and catalyze ozone molecules to generate active atomic oxygen, and has stable and efficient catalytic activity when treating new micropollutants in tail water, and meanwhile, polycrystalline iron nanoparticles are stably loaded on the surface of the porous biochar through Fe-C bonds, so that the photocatalytic activity of the porous biochar is improved. The mechanical strength and the structural stability of the catalyst can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sewage treatment, and more specifically, particularly relates to a polycrystalline iron-loaded porous biochar aerogel catalyst and a preparation method and application thereof. Background Art

[0002] The content of new pollutants in water is very low, but they are very harmful and can affect the endocrine system and genetic system of humans and other organisms. The potential harm that new pollutants may bring to the ecological environment and human health and survival has become a major research topic in the field of water treatment in this century. Therefore, it is necessary to develop a method with simple process, low cost, no residue, and no secondary pollution to remove new pollutants in water. Ozone can be used to remove color, remove odor, and sterilize water with its high oxidizing property. It is widely used in the project of repairing organic polluted water.

[0003] Although ozone has a strong oxidizing ability, it is still difficult to achieve ideal results when treating some organic substances with complex structures. Moreover, when treating some difficult-to-degrade organic substances, a large amount of ozone is often required or a long time is consumed to achieve complete degradation, which undoubtedly increases the treatment cost. Therefore, catalytic ozone oxidation is particularly important. The characteristics of the catalyst are the most important factor affecting the effect of heterogeneous catalytic ozonation process. At present, researchers at home and abroad have conducted a lot of research to develop innovative catalysts to improve the efficiency of heterogeneous catalytic ozonation. For example, alumina, natural zeolite, reduced graphene oxide, different metal-loaded catalysts and metal oxides have been used as catalysts in the catalytic ozonation process. At the same time, iron-based materials are often used as catalysts for heterogeneous catalytic ozonation due to their easy synthesis, good catalytic performance and the availability of iron in nature. In the catalytic ozonation system, the synthesis and application of iron-based materials with novel characteristics and functions have been widely studied. It is of great significance to develop a stable iron-based material to stably promote ozone oxidation.

[0004] Therefore, the method of fixing transition metals on biochar for treatment has been welcomed and paid attention to by researchers at home and abroad. For example, Jothinathan et al. (L. Jothinathana, QQ Cai, et al. Fe-Mn doped powdered activated carbon pellet as ozone catalyst for cost-effective phenolic wastewater treatment: Mechanism studies and phenol by-products elimination [J] Journal of Hazardous Materials, 424 (2022) 127483) prepared a new type of bimetallic doped polyaluminium chloride (Fe-Mn / PAC) particles by sol-gel method, and used it as an ozone catalyst for the treatment of phenolic wastewater (PWW). Using Fe-Mn / PAC particle microbubble ozone oxidation technology, the removal rates of chemical oxygen demand (COD) and phenol in PWW 1h were increased to 79% and 95%, respectively, while Fe-Mn / PAC does not have the ability to adsorb ozone. In the study by Yewen Qiu (Y.Qiu, X.Xu, Z.Xu, J.Liang, Y.Yu, X.Cao, Contribution of different iron species in the iron-biocharcomposites to sorption and degradation of two dyes with varying properties, [J] Chemical Engineering Journal 389 (2020)), iron-biochar composites have a higher ability to remove dyes than original biochar, and the removal efficiencies of methylene blue and acid orange 7 increased from 33%-72% to 48%-92% and from 49%-70% to 72%-85%, respectively. It shows that iron-biochar composites can effectively remove dyes, and iron species play an important role in dye removal. However, iron exists in a single form, mainly iron oxides, and has poor stress resistance in practical applications.

[0005] For example, Chinese patent CN202211167489 discloses a chitosan-based biochar with a porous structure and a high specific surface area, and its preparation method and application, which disperses chitosan in a mixed solvent of potassium hydroxide, urea and water, and then freeze-dries and calcined to obtain a catalyst used in the field of persulfate. Chinese patent CN202111060989 discloses a highly elastic and high-temperature resistant aerogel and its preparation method, which uses modified biochar to successively obtain aerogels through low-temperature baking, carbon dioxide microwave heating, ultrasonic treatment, electrostatic directional freeze drying and vacuum sublimation to form a porous three-dimensional network structure, giving the aerogels oil absorption and high elasticity.

[0006] The above patent applications have proven the excellent capabilities of aerogels in other fields, but these catalysts cannot provide effective support in the direction of catalyzing ozone. As one of the most promising advanced oxidation processes for practical engineering, ozone is easily decomposed into oxygen in water due to its gaseous form, which reduces its utilization rate. Therefore, one of the research focuses of ozone technology is to synthesize a high-quality ozone catalyst, which can improve ozone utilization while reducing costs, and solve practical problems in a green and efficient way. Summary of the invention

[0007] 1. Technical problem to be solved by the invention

[0008] One of the purposes of the present invention is to provide a polycrystalline iron-loaded porous biochar aerogel catalyst, wherein the biochar aerogel has a rich pore structure, thereby providing abundant adsorption and reaction active sites and electron transfer channels, thereby effectively improving the catalytic efficiency of the catalyst; the polycrystalline iron nanoparticles in the catalyst are stably loaded on the porous biochar surface through Fe-C bonds, which can effectively improve the mechanical strength and structural stability of the catalyst;

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned polycrystalline iron-loaded porous biochar aerogel catalyst, and the preparation process is simple to operate and has low production cost;

[0010] The third object of the present invention is to provide an application of the above-mentioned polycrystalline iron-loaded porous biochar aerogel catalyst in water purification, air purification, chemical catalysis and energy storage, especially when applied to an ozone catalytic purification system, it can adsorb ozone to form surface atomic oxygen, so that it can stably and efficiently play the role of electron transfer in the treatment of new pollutants in tail water.

[0011] 2. Technical solution

[0012] In order to achieve the above object, the technical solution provided by the present invention is:

[0013] The first aspect of the present invention provides a polycrystalline iron-loaded porous biochar aerogel catalyst, the internal structure of the catalyst is an overall honeycomb pore network structure, which includes a porous biochar matrix, and polycrystalline iron nanoparticles are loaded on the biochar sheet through Fe-C bonds.

[0014] The catalyst of the present invention uses a porous biochar matrix as a carrier, and the biochar matrix has a lamellar structure, and the sheets are cross-linked to form a network structure, and the biochar sheets are distributed with honeycomb-like channels, so the pore structure is relatively rich, which greatly improves the specific surface area of ​​the catalyst. Therefore, when applied to water purification, it can provide more adsorption and reaction active sites and electron migration channels for the adsorption and degradation of organic matter such as antibiotics, thereby effectively improving the degradation efficiency of organic matter such as antibiotics. At the same time, polycrystalline iron nanoparticles are uniformly loaded on the biochar sheets in the present invention, and the presence of polycrystalline iron can provide more active sites, which is conducive to improving and ensuring the catalytic effect of the catalyst; and the polycrystalline iron nanoparticles are loaded on the biochar sheets through Fe-C bonds, which can effectively improve the loading firmness of the catalyst, thereby helping to improve the mechanical strength of the entire catalyst and the stability of the catalyst, making up for the deficiency of the weak composite surface of the iron-based and carbon-based materials in the prior art.

[0015] It should be noted that the polycrystalline iron nanoparticles in the present invention are loaded on the biochar sheet through Fe-C bonds, which can be directly loaded on the biochar sheet or indirectly loaded, that is, the loading connection between the polycrystalline iron nanoparticles and the biochar sheet is achieved through a cross-linking agent. In addition, the macroscopic shape of the polycrystalline iron-loaded porous biochar aerogel of the present invention is not limited and can be changed according to actual conditions and actual needs. For example, a columnar structure (containing interconnected pores inside) such as spherical, square, columnar, blocky, etc. can be used, and an irregular shape or a film can also be used.

[0016] As a further improvement of any technical solution of the catalyst of the first aspect of the present invention, the crystal planes of the polycrystalline iron include but are not limited to the (220) crystal plane of Fe3O4, the (002) crystal plane of Fe3C, the (211) crystal plane of Fe3C, and the (031) crystal plane of Fe2O3.

[0017] As a further improvement of any technical solution of the catalyst of the first aspect of the present invention, different crystals of the polycrystalline iron are alternately grown inside the biochar sheet, and staggered network lattice stripes can be observed under a transmission electron microscope, thereby providing more sites for catalyzing ozone.

[0018] As a further improvement of any technical solution of the catalyst of the first aspect of the present invention, the content of polycrystalline iron accounts for 0.27at% to 37at% of the total amount of the catalyst, wherein Fe(III) accounts for 38at% to 54at% of the total iron content, Fe(II) accounts for 17at% to 31at% of the total iron content, and Fe3C accounts for 17at% to 31at% of the total iron content.

[0019] As a further improvement of any technical solution of the catalyst of the first aspect of the present invention, the loading amount of the polycrystalline iron nanoparticles accounts for 5-15% of the mass of the catalyst, and more preferably 10%.

[0020] As a further improvement of any technical solution of the catalyst of the first aspect of the present invention, the size of the polycrystalline iron nanoparticles is 1 to 10 nm, and more preferably 5 to 10 nm. The polycrystalline iron nanoparticles are small in size and evenly distributed, which is beneficial to further improve the catalytic effect of the catalyst.

[0021] As a further improvement of any technical solution of the catalyst of the first aspect of the present invention, the diameter of the pores on the biochar matrix is ​​50 to 100 microns, and more preferably 70 to 90 microns.

[0022] As a further improvement of any technical solution of the catalyst of the first aspect of the present invention, the contact angle of the biochar aerogel is less than 88° and has good hydrophilicity, which is beneficial to further promote the adsorption, migration, transport and degradation of organic pollutants inside the catalyst.

[0023] As a further improvement of any technical solution of the catalyst of the first aspect of the present invention, the impedance value of the biochar aerogel is below 11Ω and has a fast electron transmission capability.

[0024] As a further improvement of any technical solution of the catalyst of the first aspect of the present invention, the ID / IG value in the Raman spectrum of the biochar aerogel is greater than 0.85, and the in-situ Raman spectrum of the biochar aerogel after contacting with O3 in water is 877.74 cm -1 、935.76cm -1 and 1004.97cm -1 After the catalyst of the present invention is in contact with O3, its in-situ Raman spectrum has a peak at 877.74 cm -1 、935.76cm -1 and 1004.97cm -1 New peaks appear at both ends, corresponding to the surface atomic oxygen (O2 * , O * ) and O3 adsorbed on the surface. This is mainly because the material surface can form O after adsorbing ozone * and O2 * , O2 *It is then further converted into singlet oxygen through electron transfer.

[0025] Raman spectroscopy is used to characterize the structural characteristics of carbon material catalysts. The intensity ratio of the D band and the G band (ID / IG) can be used to analyze the degree of defects in the catalyst. The closer the ID / IG value is to 1, the higher the degree of disorder of the biochar sheet. The wrinkles, bumps and defects on the biochar sheet can not only produce redox activity, but also serve as electron transport media and reaction active sites.

[0026] The second aspect of the present invention provides a method for preparing any porous biochar aerogel catalyst as described in the first aspect of the present invention, comprising:

[0027] The iron-based biochar and the cross-linking agent are contacted / mixed in an aqueous solution to form an iron-based biochar-cross-linking agent mixture (i.e., an iron-based biochar hydrogel); wherein the iron-based biochar comprises a biochar matrix and polycrystalline iron nanoparticles supported on the biochar sheet, and the polycrystalline iron nanoparticles are physically bonded to the biochar matrix;

[0028] The iron-based biochar-crosslinking agent mixture is freeze-dried to form honeycomb-shaped pores in the biochar sheet to obtain the iron-based biochar aerogel; the iron-based biochar-crosslinking agent mixture is first frozen into ice by freeze-drying, and then sublimated to form pores in the biochar sheet;

[0029] The iron-based biochar aerogel is calcined under an inert atmosphere so that the polycrystalline iron nanoparticles are loaded on the biochar sheet through Fe-C bonds, thereby obtaining the polycrystalline iron-loaded porous biochar aerogel catalyst.

[0030] The present invention utilizes the ion exchange effect of the cross-linking agent to cross-link the iron base and the biochar sheet together, the overall preparation process is simple, the porous biochar aerogel is tightly compounded in the form of iron and carbon and has a certain mechanical strength, and can adsorb ozone to form surface atomic oxygen, so that it can stably and efficiently play the role of electron transfer in the tail water treatment of new pollutants, and improve the ozone catalytic efficiency. At the same time, the raw materials used in the preparation of this application are green and pollution-free, easy to purchase, and low in cost, easy to mass produce, and can be used in the fields of environmental organic polluted water treatment, drinking water deep purification treatment, etc.

[0031] The aerogel obtained directly by freeze-drying is relatively unstable. After low-temperature calcination, the polycrystalline iron can be firmly loaded on the porous biochar matrix. The fusion of the two carbons is conducive to ensuring the stability of the structure and preventing it from collapsing. Specifically, the cross-linking agent and the polycrystalline iron are bonded through Fe-C bonds, and the biochar and the cross-linking agent are mainly bonded through C=C / CC bonds.

[0032] As a further improvement of any technical solution of the preparation method of the second aspect of the present invention, the specific surface area of ​​the iron-based biochar (polycrystalline iron biochar) is 150 to 250 m 2 / g, which can provide abundant active sites for the adsorption and degradation of antibiotic organic pollutants, and is beneficial to improving the catalytic activity of the catalyst.

[0033] As a further improvement of any technical solution of the preparation method of the second aspect of the present invention, the cross-linking agent includes but is not limited to chitosan, carrageenan, and sodium alginate, wherein the mass ratio of the iron-based biochar to the cross-linking agent is (2-5): (1-5), and further preferably (2-5): 3.

[0034] The cross-linking agent is further preferably chitosan. Since chitosan also contains a large amount of N element, using it as a cross-linking agent can not only achieve a firm loading of polycrystalline iron nanoparticles, but also provide a nitrogen source to achieve N doping on the catalyst. Co-doping not only ensures the catalytic stability of the catalyst, but the synergistic effect between the two promotes the adsorption and catalytic degradation of antibiotic organic pollutants, and has better catalytic performance than carbon materials doped with a single element.

[0035] As a further improvement of any technical solution of the preparation method of the second aspect of the present invention, the biochar includes but is not limited to bamboo charcoal, straw biochar, and coconut shell charcoal, and is further preferably bamboo charcoal. Bamboo charcoal is not only a green and pollution-free raw material, easy to purchase, and low in cost, but also has a large specific surface area, which can provide abundant active sites for the adsorption and degradation of antibiotic organic pollutants, thereby further improving the catalytic activity of the catalyst.

[0036] As a further improvement of any technical solution of the preparation method of the second aspect of the present invention, an organic acid or an inorganic acid is added to the aqueous solution to adjust the consistency of the solution, thereby obtaining a viscous hydrogel; the organic acid or inorganic acid can be, for example, hydrochloric acid, formic acid, acetic acid, lactic acid, malic acid or ascorbic acid, preferably acetic acid, and the ratio of iron-based biochar, cross-linking agent, acetic acid, and water is (0.8g~2g):(0.8g~2g):(0.4ml~0.8ml):(38ml~35.2ml), and more preferably 1.6g:1.2g:0.8ml:36.4ml.

[0037] As a further improvement of any technical solution of the preparation method of the second aspect of the present invention, the freeze-drying treatment of the iron-based biochar-crosslinking agent mixture includes: first freezing the iron-based biochar-crosslinking agent mixture at -15 to -25°C, and then freeze-drying it at -70 to -85°C to form pores.

[0038] As a further improvement of any technical solution of the preparation method of the second aspect of the present invention, the iron-based biochar aerogel is calcined under an inert atmosphere, comprising: heating the iron-based biochar aerogel to 100°C to 200°C at a rate of 1 to 8°C / min, and cooling to room temperature after keeping the temperature for 1.0 to 2.0 hours. The inert atmosphere is high-purity nitrogen or argon with a purity of ≥99.99%.

[0039] As a further solution of any technical solution of the preparation method of the second aspect of the present invention, the iron-based biochar is prepared by chemical deposition or mechanical ball milling.

[0040] As one implementation of any technical solution of the preparation method of the second aspect of the present invention, the preparation process of the iron-based biochar specifically includes:

[0041] The iron source and biochar are mixed and dispersed in ultrapure water, and after mixing for a certain period of time at room temperature, the supernatant is removed, and the iron salt composite biochar material is obtained by drying, cooling, grinding and crushing, that is, the iron salt is combined with the surface of the biochar through electrostatic-complexation;

[0042] The iron salt composite biochar material is calcined at high temperature in an airtight condition, and then cooled and ground to obtain the iron-based biochar material. After the calcination treatment, the iron salt is decomposed at high temperature, and the polycrystalline iron is loaded on the biochar sheet.

[0043] Furthermore, the iron source is selected from one or more of ferric nitrate, ferric chloride and ferric citrate.

[0044] Furthermore, the high-temperature calcination of the iron salt composite biochar material under air-tight conditions includes: heating to 300°C to 800°C at a rate of 1 to 5°C / min, and then keeping the temperature for 1 to 4 hours; more preferably, heating to 700°C at a rate of 3°C / min, and then keeping the temperature for 3 hours. The inert atmosphere is preferably high-purity nitrogen or argon with a purity of ≥99.99%.

[0045] Furthermore, it also includes: acid washing the iron-based biochar material synthesized by high-temperature calcination, and then washing it with ultrapure water until the pH is neutral to remove unstable iron and prevent the dissolution of iron during subsequent use. It is further preferred to use sulfuric acid for acid washing, and the concentration of sulfuric acid is preferably 1 mol / L.

[0046] The third aspect of the present invention also provides a use of any porous biochar aerogel catalyst as described in the first aspect in the field of water purification, air purification or chemical catalysis.

[0047] Furthermore, the water purification system includes but is not limited to an ozone catalytic oxidation system, and its use method includes:

[0048] In the ozone catalytic oxidation system, the porous biochar aerogel catalyst is brought into contact with ozone in the water to be treated to form surface atomic oxygen, so as to catalyze the decomposition of ozone to produce singlet oxygen and hydroxyl radicals, thereby enhancing the degradation of pollutants or antibiotics in the water.

[0049] Furthermore, the water body to be treated includes both difficult-to-degrade high-concentration antibiotic pharmaceutical wastewater and low-concentration sewage treatment plant effluent, wherein the antibiotic concentration in the high-concentration antibiotic pharmaceutical wastewater is 1-100 mg / L, and the antibiotic concentration in the low-concentration sewage treatment plant effluent system is 1-20 μg / L.

[0050] 3. Beneficial effects

[0051] In summary, the technical solution provided by the present invention can achieve the following beneficial effects compared with the prior art:

[0052] (1) The present invention provides a polycrystalline iron-loaded porous biochar aerogel, which includes a porous biochar matrix and polycrystalline iron nanoparticles loaded on the matrix. The aerogel has abundant pores and a large specific surface area, and can adsorb ozone to form surface atomic oxygen, so that it can stably and efficiently play the role of electron transfer in the treatment of new pollutants in tail water, and also provides abundant active sites for the adsorption and degradation of antibiotic organic pollutants, thereby improving the ozone catalytic efficiency. In addition, in the present invention, the polycrystalline iron nanoparticles are uniformly loaded on the biochar sheet through Fe-C bonds. On the one hand, the presence of a variety of different iron-containing crystals is conducive to providing more reactive active sites. On the other hand, the polycrystalline iron nanoparticles are loaded in the form of Fe-C bonds, rather than simple physical bonding, thereby ensuring both the stable loading of polycrystalline iron and the stability of the pore structure of the aerogel, and the synergistic effect between the two also enhances the catalytic activation of ozone and the degradation and removal of antibiotic pollutants.

[0053] (2) The particle size of the polycrystalline iron nanoparticles in the present invention is 1 to 10 nm, which is small, thereby helping to further improve the ozone catalytic decomposition effect. Compared with the porous biochar aerogel material not loaded with polycrystalline iron, the polycrystalline iron loaded porous biochar aerogel has a richer pore structure, providing abundant adsorption and reaction active sites and electron transfer channels for the adsorption and degradation of antibiotic organic pollutants, thereby helping to improve the degradation efficiency of organic matter such as antibiotics.

[0054] (3) Compared with other carbon aerogel materials, the polycrystalline iron-loaded porous biochar aerogel of the present invention has better hydrophilicity, which is beneficial to further promote the adsorption, migration, transmission and degradation of organic pollutants inside the catalyst; its impedance value is below 11Ω, and it has fast electron transmission capability; at the same time, the catalyst has good elasticity and does not deform after multi-stage extrusion; it has a high ID / IG value, so the material is rich in defects, which is beneficial to the high-speed adsorption and conversion of pollutants and oxidants inside the material.

[0055] (4) In the present invention, when preparing the polycrystalline iron-loaded porous biochar aerogel, a certain cross-linking agent is added. After calcination under the action of the cross-linking agent, the polycrystalline iron nanoparticles can be loaded on the biochar sheets in the form of Fe-C bonds, thereby facilitating the improvement of the loading of the polycrystalline iron nanoparticles and the stability of the pore structure; the cross-linking agent is further preferably chitosan, which can also serve as a nitrogen source, so that the N element is evenly loaded on the aerogel, and the adsorption and catalytic degradation of antibiotic organic pollutants are promoted through carbon-nitrogen co-doping.

[0056] (5) The preparation process of the present invention is simple, low-cost, and suitable for large-scale promotion and application. The aerogel prepared can be processed into various shapes according to actual needs, such as cylindrical, spherical, block, irregular shape, film, etc.

[0057] (6) The aerogel catalyst of the present invention can be applied to water purification, air purification, chemical catalysis or energy storage. When applied to water purification, it can be applied to but not limited to ozone catalytic oxidation systems, and can be used to purify difficult-to-degrade high-concentration antibiotic pharmaceutical wastewater, and can also be used to purify low-concentration sewage treatment plant effluent. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 (a) is a scanning electron microscope image of the aerogel prepared in Example 4, (b) is a scanning electron microscope image of the aerogel obtained in Comparative Example 1, (c), (d), (e) and (f) are transmission electron microscope images of the aerogel obtained in Example 4;

[0059] Figure 2 The scanning electron microscope images of the aerogels obtained in Comparative Example 2 and Examples 2, 3 and 5;

[0060] Figure 3 This is a SEM energy spectrum analysis diagram of the aerogel prepared in Example 4;

[0061] Figure 4 (a) and (b) are the pressure test results of the aerogels prepared in Example 4 and Comparative Example 1, respectively, and (c) to (h) are the contact angles of the aerogels in Comparative Example 1, Comparative Example 2, and Examples 2-5, respectively;

[0062] Figure 5 This is the full X-ray photoelectron spectrum of the aerogel obtained in Example 2-5.

[0063] Figure 6 (a) is the Raman spectrum of the aerogel obtained in Examples 2-5; (b) is the in-situ Raman spectrum of Example 4.

[0064] Figure 7 The impedance diagram of the aerogels obtained in Comparative Example 1 and Example 4.

[0065] Figure 8 (a) is a schematic diagram of different carbon ratios of the aerogels obtained in Example 2-5; (b) is a schematic diagram of different nitrogen ratios of the aerogels obtained in Example 2-5; (c) is a schematic diagram of different oxygen ratios of the aerogels obtained in Example 2-5; (d) is a schematic diagram of different iron ratios of the aerogels obtained in Example 2-5.

[0066] Fig. 9 The relationship between different proportions of components in the aerogels obtained in Examples 2-5 and the catalytic efficiency.

[0067] Fig.10 (a) is the kinetic curve of levofloxacin degradation catalyzed by different aerogels, and (b) is the kinetic fitting of levofloxacin degradation catalyzed by different aerogels.

[0068] Fig.11 (a) is the free radical quenching experimental result of aerogel degradation of levofloxacin in Example 4, (b) is the electron paramagnetic resonance spectrum of singlet oxygen in the process of aerogel degradation of levofloxacin in Example 4, (c) is the electron paramagnetic resonance spectrum of hydroxyl radicals in the process of aerogel degradation of levofloxacin in Example 4, (d) is the electron paramagnetic resonance spectrum of superoxide ion radicals in the process of aerogel degradation of levofloxacin in Example 4.

[0069] Fig.12 These are the experimental results of the reuse of aerogel-catalyzed ozone degradation of levofloxacin in Example 4.

[0070] Fig.13 These are the experimental results of aerogel-catalyzed ozone degradation of antibiotics in tail water in Example 4. DETAILED DESCRIPTION

[0071] The present invention provides a polycrystalline iron-loaded porous biochar aerogel catalyst, the catalyst comprises a porous biochar matrix and polycrystalline iron nanoparticles uniformly distributed on the biochar matrix, the porous biochar matrix and the polycrystalline iron nanoparticles together constitute a polycrystalline iron biochar material, wherein the catalyst as a whole presents a honeycomb pore network structure (i.e., the biochar sheets are cross-linked to form a three-dimensional network structure, and there are interconnected pores inside), the pore structure is rich, the specific surface area is large, ozone can be adsorbed to form surface atomic oxygen, and abundant active sites are provided for the adsorption and degradation of organic pollutants such as antibiotics, thereby facilitating the degradation efficiency of organic substances such as antibiotics. The polycrystalline iron nanoparticles are uniformly loaded on the biochar sheets through Fe-C bonds, thereby not only promoting the adsorption and catalytic degradation of organic pollutants such as antibiotics, further improving the catalytic efficiency, but also effectively ensuring the firmness of the polycrystalline iron nanoparticle loading, facilitating the improvement of the overall mechanical strength of the catalyst, and then ensuring the catalytic stability of the catalyst.

[0072] As a further preferred embodiment of the polycrystalline iron-supported porous biochar aerogel catalyst of the present invention, the specific surface area of ​​the polycrystalline iron biochar material is 150 to 250 m 2 / g, the diameter of the pores on the biochar matrix is ​​50-100 microns, more preferably 70-90 microns. In some embodiments, the size (particle diameter) of the polycrystalline iron nanoparticles is 1-10 nm, more preferably 5-10 nm.

[0073] The crystal planes of the polycrystalline iron include but are not limited to the (220) crystal plane of Fe3O4, the (002) crystal plane of Fe3C, the (211) crystal plane of Fe3C and the (031) crystal plane of Fe2O3. As a further preferred embodiment of the polycrystalline iron-loaded porous biochar aerogel catalyst of the present invention, the loading amount of polycrystalline iron nanoparticles accounts for 5-15% of the mass of the catalyst or the content of polycrystalline iron accounts for 0.27at% to 37at% of the total amount of the catalyst, wherein Fe(III) accounts for 38at% to 54at% of the total iron content, Fe(II) accounts for 17at% to 31at% of the total iron content, and Fe3C accounts for 17at% to 31at% of the total iron content.

[0074] In order to further understand the content of the present invention, the present invention is now described in detail in conjunction with specific embodiments. Part of the equipment and instruments used in the experimental process of each embodiment are shown in Table 1-1 below.

[0075] Table 1-1 List of instruments

[0076]

[0077]

[0078] Some of the detection experiments and their operation instructions involved in the embodiments of the present invention are as follows:

[0079] 1. Transmission electron microscopy analysis (TEM)

[0080] The present invention disperses the uniformly ground aerogel powder into an ethanol solution after passing it through a 100-mesh sieve, and ultrasonicates it until the material particles are invisible to the naked eye; the treated sample is dripped onto a copper mesh grid, and irradiated with an infrared lamp to quickly evaporate the ethanol solution and dry the sample. The experiment observed the lamellar structure on the surface of the biochar aerogel and the nanoparticles of transition metal iron inside the aerogel at different magnifications, and the crystal structure of iron was identified by observing the crystal diffraction rings formed by polycrystalline iron and the lattice fringes of iron metal nanoparticles.

[0081] 2. X-ray diffraction analysis (XRD)

[0082] The X-ray diffraction analysis of the present invention adopts a Cu target, sets the angle within the range of 20 to 80 degrees, and the scanning speed is 10 degrees / min. CS, Fe-BC, 4BC / 3CS, 2Fe-BC / 3CS, 3Fe-BC / 3CS, 4Fe-BC / 3CS, and 5Fe-BC / 3CS materials are pressed into uniform thin sheets using a small tablet press and then tested.

[0083] 3. Micro FTIR

[0084] The functional groups and chemical structures inside the catalyst are qualitatively analyzed by microscopic infrared spectroscopy, and the types of chemical elements and the purity of the substances are semi-quantitatively analyzed. In the present invention, CS, 4BC / 3CS, 2Fe-BC / 3CS, 3Fe-BC / 3CS, 4Fe-BC / 3CS, and 5Fe-BC / 3CS materials are pressed uniformly using a small tablet press and then cut into small pieces for observation.

[0085] 4. X-ray Photoelectron Spectroscopy (XPS)

[0086] The present invention uses a small tablet press to press 4BC / 3CS, 2Fe-BC / 3CS, 3Fe-BC / 3CS, 4Fe-BC / 3CS, and 5Fe-BC / 3CS materials, and then cuts them into small pieces for observation, and analyzes the influence of different amounts of powdered biochar added on the proportions of C, N, O, and Fe elements in the aerogel material.

[0087] 5. Electrochemical impedance spectroscopy (EIS)

[0088] Electrochemical impedance spectroscopy studies the relationship between AC impedance and frequency by applying a small-amplitude sinusoidal AC excitation signal to an electrochemical cell in equilibrium or under stable DC polarization conditions. The impedance value (EIS) of the catalyst can reflect its electron transfer ability. 5 mg of aerogel catalyst powder, 400 μL of ultrapure water, 400 μL of ethanol and 5 μL of Nafion were mixed, and then ultrasonically treated for 30 min to obtain the corresponding dispersion; then 200 μL of the suspension was dropped on FTO conductive glass (1.5 cm × 1.5 cm) and baked dry under infrared light. A three-electrode system (counter electrode, platinum electrode; reference electrode, Ag / AgCl; working electrode, FTO) was used, and the electrolyte solution was 0.5 mol / L Na2SO4 solution.

[0089] 6. In-situ Raman Analysis (IS-Raman)

[0090] In-situ Raman is the use of a high-resolution laser Raman instrument to characterize the ongoing reaction, including an in-situ electrochemical Raman cell and a Raman spectrometer. Before the experiment, a 532nm green laser was vertically aligned with the side of a dual-channel quartz cuvette (7.5×12.5×45mm, capacity: 1.75mL) to allow the laser to pass through the cuvette. At the beginning of the experiment, a certain amount of aerogel catalyst was added to the quartz cuvette, and an ozone aqueous solution was added through a syringe. The quartz cuvette was then sealed with a lid and gently shaken to ensure that the solid catalyst was evenly suspended. After sufficient reaction, the Raman laser was started, and the emission scan range was 200 to 1200cm -1 , resolution 2cm -1 In the experiment, laser irradiation did not cause ozone decomposition. For comparison, ultrapure water and an aqueous solution saturated with oxygen were added to replace the ozone aqueous solution in the same procedure.

[0091] 7. Electron Paramagnetic Resonance (EPR)

[0092] EPR is a magnetic resonance technology based on unpaired electron magnetic moments. It can be used to qualitatively and quantitatively detect unpaired electrons in substances, and further study the structural properties of materials. At the beginning of the reaction, unsaturated antimagnetic functional groups (such as 5,5-dimethyl-1-pyrroline-N-oxide) are added to the reaction system, combined with EPR spectroscopy technology, and again combined with the specific peak shape of free radicals to detect the ·OH produced by the system, and its peak shape is 1:2:2:1. In this experiment, EPR was used to detect TEMP (2,2,6,6-tetramethyl-4-piperidone hydrochloride), DMPO (5,5-dimethyl-1-pyrroline-N-oxide), and MeOH (methanol) 30sec and 60sec after the start of the degradation reaction. 1 O2, ·OH and ·O2 -Capture and detect the active oxygen species produced by the 4Fe-BC / 4CS&O3 system.

[0093] Example 1

[0094] A polycrystalline iron-loaded porous biochar aerogel catalyst of this embodiment includes a porous biochar matrix and polycrystalline iron nanoparticles uniformly distributed on the biochar matrix, wherein the porous biochar matrix and the polycrystalline iron nanoparticles together constitute a polycrystalline iron biochar material, wherein the catalyst as a whole presents a honeycomb pore network structure, and the polycrystalline iron nanoparticles are uniformly loaded on the biochar sheet through Fe-C bonds. Compared with the porous carbon material not doped with polycrystalline iron, the polycrystalline iron-loaded porous biochar aerogel has a richer pore structure, which can provide more adsorption and reaction active sites and electron migration channels for the adsorption and degradation of organic matter such as antibiotics.

[0095] Specifically, the macroscopic appearance of the polycrystalline iron-loaded porous biochar aerogel in this embodiment is a black column (the production mold can be replaced according to actual needs to produce products with different appearances), and the specific surface area of ​​the polycrystalline iron biochar material is 150-250m 2 / g, the diameter of the pores on the biochar matrix is ​​70-90 microns, the size (particle size) of the polycrystalline iron nanoparticles is 5-10nm, and the crystal planes of the polycrystalline iron include but are not limited to the (220) crystal plane of Fe3O4, the (002) crystal plane of Fe3C, the (211) crystal plane of Fe3C and the (031) crystal plane of Fe2O3.

[0096] The loading amount of the polycrystalline iron nanoparticles accounts for 5-15% of the catalyst mass or the content of polycrystalline iron accounts for 0.27at%-37at% of the total catalyst mass, wherein Fe(III) accounts for 38at%-54at% of the total iron content, Fe(II) accounts for 17at%-31at% of the total iron content, and Fe3C accounts for 17at%-31at% of the total iron content.

[0097] The contact angle of the biochar aerogel in this embodiment is less than 88°, and its impedance value is below 11Ω. The ID / IG value in the Raman spectrum of the biochar aerogel is greater than 0.85. After contacting with O3 in water, the in-situ Raman spectrum of the biochar aerogel is 877.74cm -1 、935.76cm -1 and 1004.97cm -1 New peaks appear everywhere.

[0098] Example 2

[0099] This embodiment provides a method for preparing a polycrystalline iron-supported porous biochar aerogel catalyst, comprising the following steps:

[0100] (1) 5 g of bamboo charcoal was used as the biochar source, and 160 g of nonahydrate and ferric nitrate were used as the iron source. After weighing, 200 ml of ultrapure water was selected and mixed, and 10 ml of 1 M nitric acid was added to prevent iron hydrolysis. The mixture was mixed at room temperature for 8 h, the supernatant was removed, and the mixture was dried in an oven overnight. After that, the mixture was ground through a 100-mesh sieve and calcined in a tubular furnace under the protection of inert gas. The temperature was raised to 700 °C at a rate of 3 °C / min during the calcination process. The mixture was kept warm for 3.0 h to obtain a polycrystalline iron biochar material, which was recorded as Fe-BC.

[0101] (2) Weigh 0.8 g of polycrystalline iron biochar and 1.2 g of chitosan as a nitrogen source and binder, put them into a beaker, add 37.2 ml of deionized water, add 0.8 ml of glacial acetic acid, and then place the beaker on a magnetic stirrer and stir for 60 minutes. After mixing evenly, ultrasonicate for 10 minutes.

[0102] (3) Take 1 ml of the sample in (2), add it dropwise into a cryotube, and freeze it in a -20°C refrigerator until it becomes non-flowing; then place it in a freeze dryer at -80°C and freeze-dry for 24 h.

[0103] (4) A certain amount of the sample in step (3) above was placed in a custom crucible, placed in a high-temperature tube furnace in a N2 atmosphere, heated to 150°C at a rate of 5°C / min, and kept at that temperature for 80 min, and then naturally cooled to room temperature to obtain polycrystalline iron-loaded porous biochar aerogel, recorded as 2Fe-BC / 3CS.

[0104] Example 3

[0105] The preparation method of the polycrystalline iron-loaded porous biochar aerogel catalyst of this embodiment is basically the same as that of Example 2, except that: in step (2) of this embodiment, the amount of polycrystalline iron biochar added is 1.2 g, and the amount of deionized water added is 36.8 ml. The polycrystalline iron porous biochar aerogel prepared is recorded as 3Fe-BC / 3CS.

[0106] Example 4

[0107] The preparation method of the polycrystalline iron-loaded porous biochar aerogel catalyst of this embodiment is basically the same as that of Example 2, except that: in step (2) of this embodiment, the amount of polycrystalline iron biochar added is 1.6 g, and the amount of deionized water added is 36.4 ml. The polycrystalline iron porous biochar aerogel prepared is recorded as 4Fe-BC / 3CS.

[0108] Example 5

[0109] The preparation method of the polycrystalline iron-loaded porous biochar aerogel catalyst of this embodiment is basically the same as that of Example 2, except that: in step (2) of this embodiment, the amount of polycrystalline iron biochar added is 2 g, and the amount of deionized water added is 36 ml. The polycrystalline iron porous biochar aerogel prepared is recorded as 5Fe-BC / 3CS.

[0110] Comparative Example 1

[0111] (1) Weigh 1.2 g of chitosan into a beaker, add 38 ml of deionized water, add 0.8 ml of glacial acetic acid, and then place the beaker on a magnetic stirrer and stir for 60 min. After mixing evenly, ultrasonicate for 10 min.

[0112] (2) Take 1 ml of the sample in step (1), add it dropwise into a cryopreservation tube, place it in a refrigerator at -20°C and freeze it into a non-flowing state, then place it in a freeze dryer at -80°C and freeze-dry for 24 hours.

[0113] (3) A certain amount of the sample in step (2) was placed in a crucible, and then placed in a high-temperature tube furnace in a N2 atmosphere. The temperature was raised to 150°C at a rate of 5°C / min and kept at that temperature for 80 min. The temperature was then naturally cooled to room temperature to obtain a porous chitosan aerogel, which was recorded as CS.

[0114] Comparative Example 2

[0115] (1) Weigh 1.6 g of bamboo charcoal and 1.2 g of chitosan, put them into a beaker, add 36.4 ml of deionized water, add 0.8 ml of glacial acetic acid, place the beaker on a magnetic stirrer and stir for 60 min. After mixing evenly, place it in an ultrasonic bath for 10 min.

[0116] (2) Take 1 ml of the sample in step (1), add it dropwise into a cryopreservation tube, place it in a refrigerator at -20°C and freeze it into a non-flowing state, then place it in a freeze dryer at -80°C and freeze-dry for 24 hours.

[0117] (3) A certain amount of the sample in step (2) above was placed in a crucible, which was then placed in a high-temperature tube furnace in a N2 atmosphere, and heated to 150°C at a rate of 5°C / min, and then kept at that temperature for 80 min, and then naturally cooled to room temperature to obtain a porous biochar aerogel, which was recorded as 4BC / 3CS.

[0118] Comparative Example 3

[0119] The main difference between this comparative example and Example 4 is that in step (1), straw is used as the biochar source and ferrocene is used as the iron source to first prepare ferrocene biochar material, denoted as Ferrocene-BC; then chitosan is used as the nitrogen source and adhesive, and ferrocene biochar aerogel is obtained by freeze-drying and calcining, denoted as 4Ferrocene-BC / 3CS. The other preparation processes are basically the same as those in Example 4.

[0120] Comparative Example 4

[0121] The difference between this comparative example and Example 4 is that in step (1), straw is used as the biochar source and ferric chloride is used as the iron source to first prepare ferric chloride biochar material, recorded as 4Ferric chloride-BC; then chitosan is used as the nitrogen source and adhesive, and after freeze-drying and calcination, ferric chloride biochar aerogel is obtained, recorded as 4Ferric chloride-BC / 3CS. The other preparation processes are basically the same as those in Example 4.

[0122] like Figure 2 (a), (b), (c), and (d) are SEM images of the aerogels obtained in Comparative Example 2, Example 2, Example 3, and Example 5, respectively. Figure 1 (a) shows the SEM image of the product in Example 4. By comparison, it is found that the biochar aerogel doped with polycrystalline iron has more uniform pores, and the pores formed by the direct composite of iron-free biochar and chitosan are larger and pulled into an uneven shape, and are not formed ( Figure 2 (a)). The biochar aerogel formed by the composite of iron-based biochar and chitosan has uniform pores, and as the amount of iron-based biochar added increases, the biochar sheets gradually become rougher and the degree of defects increases.

[0123] like Figure 1 (b) shows a scanning electron microscope (SEM) image of undoped chitosan porous aerogel CS (Comparative Example 1). Low-viscosity chitosan is dispersed in an acetic acid aqueous solution to form a colloid, and then freeze-dried by freeze-drying to form a porous honeycomb structure with a pore size of about 80 microns, but the CS sheet is smooth and flat, with a low degree of defects, and provides fewer catalytic reaction active sites. Adding chitosan as a cross-linking agent to the iron-based biochar material can utilize the cross-linking effect of chitosan to stably connect the biochar sheet and polycrystalline iron particles to form a loose, porous, water-stable biochar porous aerogel material, and its pore structure is relatively rough, thereby effectively improving the electron transfer rate and providing abundant reaction sites for the catalytic reaction of ozone.

[0124] Figure 1 (c) shows a TEM scan of the prepared 4Fe-BC / 3CS, where the iron particle size is observed to be 5-7 nm. Figure 1 As shown in (d) and (e), TEM also proves the existence of polycrystalline iron. Multiple crystals grow alternately inside the biochar layer, which can provide more sites for catalytic ozone. Since there are multiple grains in the material crystal, each grain has a different crystal face, so multiple diffraction rings will appear in the diffraction pattern. Figure 1The diffraction ring calibration in the area (a) shows that ( Figure 1 f), the diffraction radius from inside to outside is (220) crystal plane of Fe3O4, (002) crystal plane of Fe3C, e3 The (211) crystal plane of C and the (031) crystal plane of Fe2O3.

[0125] like Figure 3 The SEM spectrum analysis diagram of the aerogel in Example 4 is shown. Figure 3 As can be seen in d and e, chitosan as an adhesive forms the main framework of the pores, while iron ( Figure 3 f) is evenly distributed throughout the material, indicating that the iron inside the catalyst is evenly distributed, and a 3D porous structure is formed by chitosan bonding biochar. That is, by adding a cross-linking agent, on the one hand, the polycrystalline iron is firmly loaded on the porous biochar matrix through Fe-C bonds, and on the other hand, the cross-linking agent is used to bond the porous biochar sheets to each other to form a 3D porous skeleton structure.

[0126] like Figure 4 As shown in (a) and (b), compared with the undoped chitosan porous aerogel CS (Comparative Example 1), the expansion multiple of the aerogel 4Fe-BC / 3CS doped with polycrystalline iron biochar (Example 4) increased from 1.05 times to 1.3 times, and after multiple compressions, it still maintained its original morphology without particle peeling, indicating that the material has good softness, resilience and plasticity, and the connection between the biochar sheets is relatively strong. This may be due to the fact that after the addition of biochar, the material has a more stable structure through surface complexation, π-π interaction and hydrogen bonding, and the elasticity and plasticity provide a higher possibility for the material in practical application.

[0127] Figure 4 In (ch), the contact angle test and the corresponding absorption time of the aerogel obtained in Comparative Example 1, Comparative Example 2 and Examples 2-5 are respectively shown. It can be seen from the figure that the absorption time can be reduced to 0.34s after the introduction of biochar. This may be due to the fact that after the introduction of the biochar material, the surface-rich O and C functional groups make the material have a better water absorption rate for water, but the contact angle angle has hardly changed (89.8°). After the introduction of polycrystalline iron biochar, the contact angle and water absorption time of the composite material are significantly reduced, indicating that the hydrophilicity and water absorption performance of the aerogel are greatly improved after the introduction of iron-based biochar. This may be related to the change in the amount of oxygen-containing functional groups on the surface of the iron-based biochar aerogel after calcination heat treatment. Heat treatment can improve the hydrophilicity of the biochar material. The improvement of hydrophilicity and water absorption rate allows pollutants to pass through the internal pores of the material while reacting rapidly with the material inside the pores, effectively improving the exchange rate and providing conditions for high-speed ion reactions.

[0128] like Figure 5 As shown, the X-ray photoelectron spectrum of the aerogel obtained in Examples 2-5 has a peak of C1s (about 283.60eV), a peak of N1s (about 400.00eV), a peak of O1s (about 531.93eV) and a peak of Fe2p (about 722.02 and 710.81eV), and no peaks of other impurities are shown, which confirms that Fe is successfully incorporated into the C skeleton without any other products. The strength of the peak shows the content of elements in the material to a certain extent. The surface composition, chemical state and molecular structure information of the catalyst can be better understood through the XPS spectrum. The full XPS spectrum of different doping ratios further proves that Fe, C, O, and N elements are the main components of Example 4. The nitrogen content of pure biochar is extremely low. After the introduction of chitosan, due to the rich nitrogen content inside the chitosan, the aggregation of nitrogen functional groups is provided, and a large number of active oxygen functional groups are also fixed.

[0129] like Figure 6 As shown in (b), Raman spectroscopy is used to characterize the structural characteristics of carbon material catalysts. The D band (~1350cm -1 ) and G band (~1580cm -1 ) respectively characterize the defects and crystallinity of sp3 hybridized carbon. Therefore, the intensity ratio of D band and G band (ID / IG) can be used to analyze the degree of catalyst defects. The test results in the figure show that the ID / IG value follows Example 4 (0.99) > Example 2 (0.951) > Example 3 (0.92) > Example 5 (0.87). The closer the ID / IG value is to 1, the higher the degree of disorder of the biochar sheet. This not only produces redox activity, but also can be used as an electron transport medium and reaction active site. With the increase of the amount of polycrystalline iron biochar added, the ID / IG value first increases and then decreases, which shows that the iron doping amount needs to be within an appropriate limit to achieve the maximum catalytic effect.

[0130] In situ Raman spectroscopy further revealed the dissociation process of O3 on the surface Fe site, such as Figure 6 As shown in (a), after adding O3, 877.74cm -1 、935.76cm -1 and 1004.97cm -1 New peaks appeared, corresponding to the surface atomic oxygen (O2*, O*) and surface adsorbed O3. In contrast, this phenomenon was not observed in the suspension with added O2 and ultrapure water, which is mainly attributed to the adsorption of ozone on the surface of the material to form O * and O2 * , O2 * It is then further converted into singlet oxygen through electron transfer.

[0131] like Figure 7The impedance diagrams of the aerogels prepared in Example 4 and Comparative Example 1 and the polycrystalline iron biochar material Fe-BC are shown. It can be seen from the figure that the Nyquist distribution of the EIS of different materials was measured experimentally, and the diameter of the extrapolated semicircle obtained by the algorithm was used as the accurate value of the impedance. Among the four materials, Rct is CS (15.28Ω)>4BC / 3CS (11.91Ω)>Fe-BC (12.96Ω)>4Fe-BC / 3CS (10.29Ω) from large to small. This may be due to: biochar itself has good electrical conductivity, and the conductivity is enhanced after the metal ion iron is added to the biochar, and after the iron-based biochar is added to the chitosan, a continuous network structure is formed, and electron transmission channels with good electrical conductivity are established between the molecules. These channels can provide electron movement paths, thereby promoting the transport and conduction of charges. Therefore, this is also the reason why 4Fe-BC / 3CS can efficiently catalyze the degradation of new organic pollutants by ozone.

[0132] like Figure 8 As shown, the nitrogen content of pure biochar is extremely low. After the introduction of chitosan, the rich nitrogen content inside chitosan provides the aggregation of nitrogen functional groups and also fixes a large number of active oxygen functional groups. Figure 8 The detailed image of N1s in (b) classifies the doped N species into: pyridinic N (398.2 eV), Co-Nx (399.0 eV), pyrrolic N (399.9 eV), graphitic N (401.1 eV) and oxidized N (402.7 eV). With the increase of the doping amount of polycrystalline iron biochar, the pyridinic nitrogen content reaches 65% (Example 4). In addition, Figure 8 (d) It can be seen that the Fe X -C has a lower peak, and Fe X -C began to increase, and with the increase of the amount of iron-based biochar doping, the Fe X -C content is stable at around 22%, and the divalent iron content reaches 31% of the total iron content. Figure 8 (a) It can be seen that the chitosan aerogel Fe after freeze drying and secondary calcination X -C peak height began to increase significantly, and with the increase of Fe-based biochar addition X The -C peak height gradually increases to 36%-39%, which is not found in Fe-BC. Figure 8 (c) shows that the ratio of iron to oxygen under different iron-based biochar ratios is stable at 18%-26%, and reaches the maximum at 4Fe-BC / 3CS.

[0133] In order to further analyze the reasons for the improved catalytic performance, the logarithm of the degradation rate (log(k)) and the catalyst structural properties were fitted and analyzed (e.g. Fig. 9The results show that the nitrogen content of pyridine log(k)(R 2 =0.998) showed a good linear correlation ( Fig. 9 (a)), and the k value increases with the increase of pyridinic nitrogen content, which is consistent with previous experiments, indicating that pyridinic nitrogen is the catalytic site of ozone. In addition, the Fe-C group content is positively linearly related to log(k) (R 2 =0.974)( Fig. 9 (c)), indicating that Fe-C on the catalyst can well adsorb ozone to form surface atomic oxygen, and the direct reaction between O3 molecules and Fe3C produces surface atomic oxygen species. The Fe-O groups on the catalyst surface are rich in electrons and are also positively linearly correlated with log(k) (R 2 =0.911)( Fig. 9 (b)), which drives the electron transfer pathway and promotes 1 The formation of O2 and OH.

[0134] like Fig.10 As shown in (a), the ozone activation efficiency of different systems was evaluated. Levofloxacin LEV was used as a model pollutant and a comparative experiment of multiple systems was conducted. In addition, according to the established pseudo-first-order reaction kinetics ( Fig.10 (b) The apparent rate constant K was calculated. The results show that: Comparative Example 1 has no ability to adsorb and remove LEV; after the introduction of biochar, the adsorption capacity of the aerogel in Comparative Example 2 is improved, but it cannot catalyze the degradation of LEV by ozone; in the aerogel and ozone system using Example 4, at a reaction rate of 0.0929 min -1 Under the conditions of , levofloxacin can be completely removed in only 40 seconds. It is 1.75 times higher than that of Fe-BC alone, indicating that the abundant pores inside the aerogel provide feasibility for the reaction sites. The results show that the non-metallic biochar aerogel framework has almost no catalytic effect on ozone, while the pure iron-based biochar has limited activation ability for catalytic ozone. This may be because after the formation of a stable three-dimensional structure, additional doping centers are provided for the active components, which accelerates the transfer rate of electrons inside the material. In addition, the iron ion dissolution in the Fe-BC and ozone system is 0.07 mg / L, which is about 35 times higher than that of the system in Example 4 (2.1 μg / L). If used for a long time, it will inevitably bring serious ecological risks.

[0135] In order to explore the catalytic performance of catalysts with different iron-based biochar doping ratios, biochar aerogels with different iron-based biochar doping ratios were subjected to catalytic ozone experiments. Fig.10 As shown in (c), according to the pseudo-first-order reaction kinetics ( Fig.10 The apparent rate constant K was calculated as shown in (d). As the doping amount of iron-based biochar gradually increased, the reaction rate also increased from 0.050min-1 Gradually increased to 0.056min -1 , until 4Fe-BC / 3CS increased to 0.093min -1 However, the reaction rate of 5Fe-BC / 3CS dropped to 0.060min -1 This may be due to the dilution effect of active sites caused by the continuous increase in doping amount, that is, the introduction of dopants increases the distance between active sites, reducing the density of active sites and catalytic activity. XPS results also prove this point of view. The actual iron doping amount of 4Fe-BC / 3CS and 5Fe-BC / 3CS is similar ( Figure 8 ), but the contents of pyridinic nitrogen and divalent iron in 5Fe-BC / 3CS decreased, and when the material was prepared, it was found that the chitosan surface in 5Fe-BC / 3CS aerogel could not wrap the iron-based biochar powder, indicating that the covalent bond between the iron-based biochar powder and chitosan had reached a certain degree of saturation. Further adding the content of iron-based biochar was of little significance, but would block the pores in the aerogel, leading to lattice distortion and unstable crystal structure of the catalyst material, thereby affecting the exposure and activity of the active sites.

[0136] In order to understand the contribution of different oxidative active substances in the examples, the present invention uses the aerogel in Example 4 as an example to conduct a free radical quenching experiment to explore the mechanism of the aerogel catalytic ozone degradation of levofloxacin. Commonly used quenching agents furfuryl alcohol (FFA), p-chlorobenzoic acid (pCBA), potassium iodide (KI), and chloroform (CHCl3) are used as 1 O2, OH, electrons, O2 ·- The quencher, such as Fig.11 (a) After adding FFA, only 10.1% of LEV was degraded within 60 seconds, and the reaction was significantly inhibited, with the reaction rate dropping to 0.002 min. -1 In addition, pCBA, as a scavenger of ·OH in the ozone system, was added to the reaction. Only 19.7% of LEV was degraded within 60 seconds, which also inhibited the reaction to a great extent. Considering that iron can be transformed into polycrystalline states to promote the electron transfer process, KI was introduced as a chemical probe to block the electron transfer pathway. It was found that consistent with the FFA quenching experiment, only 10% of LEV was degraded, indicating that blocking the electron transfer process greatly affected the 1 The addition of CHCl3 into the system only slightly inhibited the experiment, indicating that O2 ·- It is not the main active species in the 4Fe-BC / 3CS&O3 system.

[0137] EPR was used to visually verify the ROS (reactive oxygen species) involved in the Example 4 & levofloxacin system. No different types of ROS were detected in the simple Example 4 and O3 system, indicating that the simple ozone system is a homogeneous system catalyzed by pure ozone. However, a large amount of ROS was generated in the Example 4 & O3 system. 1 O2 is trapped by TEMP (2,2,6,6-tetramethylpiperidinyl oxide), showing a typical (1:1:1) EPR spectrum with three lines of equal intensity ( Fig.11 (b) ), ·OH is captured by DMPO (5,5-dimethyl-1-pyrroline-N-oxide), showing an obvious 1:2:2:1 signal peak ( Fig.11 (c)). In addition, DMPO was added to methanol to capture O2 ·- Only a mild signal peak was produced ( Fig.11 (d)). Therefore, it can be concluded that Example 4 & O3 system can generate a large amount of ROS, promoting the effective degradation of levofloxacin, while Example 4 or O3 system alone cannot generate enough ROS to be captured in a short time.

[0138] One of the important evaluation criteria for practical applications is the reusability and stability of the material. The aerogel obtained in Example 4 showed excellent reusability, maintaining a degradation rate of 100% in ten cycles ( Fig.12 (a)). And if Fig.12 As shown in (b), the iron ion leaching is 2.14 μg / L, which is far lower than the 0.3 mg / L required by the Chinese Drinking Water Standard (GB 5749-2022). In addition, the average reaction rate of 10 cycles is 0.076 min -1 Therefore, compared with earlier studies, 4Fe-BC / 3CS is a more stable material and can be reused many times, and the above findings demonstrate the potential of this catalytic material in practical wastewater treatment.

[0139] In addition, in order to prove the feasibility of practical application, the actual rural tailwater was taken as the background, and 16 antibiotics in the water were measured using the standard (DB37 / T3738-2019), and they were classified to investigate the feasibility of the aerogel catalytic ozone degradation of different types of antibiotics. Fig.13 As shown, after ozone catalysis by the material of the present invention, sulfonamides, macrolides, tetracyclines and Class III carcinogens in the list of carcinogens published by the World Health Organization's International Agency for Research on Cancer were reduced to below 10 ng / L. Fluoroquinolones were greatly affected by actual root secretions, but the overall amount showed a downward trend.

[0140] Example 6

[0141] The preparation method of the polycrystalline iron-supported porous biochar aerogel catalyst of this embodiment comprises the following steps:

[0142] (1) Bamboo charcoal was used as a biochar source and ferric chloride was used as an iron source. They were mixed and dispersed in ultrapure water, and hydrochloric acid was added to prevent iron hydrolysis. The mixture was mixed at room temperature for 10 h, the supernatant was removed, and the mixture was dried in an oven overnight. The mixture was then ground through a 100-mesh sieve and calcined in a tubular furnace under the protection of an inert gas. The temperature was raised to 800 °C at a rate of 5 °C / min and kept at this temperature for 1.0 h to obtain a polycrystalline iron biochar material.

[0143] (2) Weigh 1.4 g of polycrystalline iron biochar and 1.2 g of chitosan as a nitrogen source and binder, put them into a beaker, add 36.6 ml of deionized water, add 1 ml of glacial acetic acid, and then place the beaker on a magnetic stirrer and stir for 50 minutes. After mixing evenly, ultrasonicate for 12 minutes.

[0144] (3) Take 1 ml of the sample in step (2), add it dropwise into a cryopreservation tube, and freeze it in a refrigerator at -20°C until it becomes non-flowing; then place it in a freeze dryer at -80°C and freeze-dry for 22 hours.

[0145] (4) Take a certain amount of the sample in the above step (3) and put it into a crucible, put it into a high-temperature tube furnace in a N2 atmosphere, heat it to 100°C at a heating rate of 1°C / min, keep it warm for 120 minutes, and then cool it naturally to room temperature to obtain polycrystalline iron-loaded porous biochar aerogel. In this embodiment, due to the high solubility of ferric chloride, it can be compounded with biochar at a high concentration, and magnetic iron oxide is formed after high-temperature oxidation. Therefore, compared with Example 4, the iron clusters are larger and the catalytic performance is slightly reduced.

[0146] Example 7

[0147] The preparation method of the polycrystalline iron-supported porous biochar aerogel catalyst of this embodiment comprises the following steps:

[0148] (1) Bamboo charcoal was used as the biochar source and ferric citrate was used as the iron source. They were mixed and dispersed in ultrapure water, and 15 ml of citric acid was added to prevent iron hydrolysis. The mixture was mixed at room temperature for 12 h, the supernatant was removed, and the mixture was dried in an oven overnight. The mixture was then ground through a 100-mesh sieve and calcined in a tubular furnace under the protection of an inert gas. The temperature was raised to 300 °C at a rate of 1 °C / min and kept at this temperature for 4.0 h to obtain a polycrystalline iron biochar material.

[0149] (2) Weigh 1.5 g of polycrystalline iron biochar and chitosan as a nitrogen source and binder, weigh 1.5 g, put it into a beaker, add 35.8 ml of deionized water, add 0.7 ml of glacial acetic acid, and then place the beaker on a magnetic stirrer and stir for 70 minutes. After mixing evenly, ultrasonicate for 8 minutes.

[0150] (3) Take 1.5 ml of the sample in step (2), add it dropwise into a cryopreservation tube, and freeze it in a refrigerator at -20°C until it becomes non-flowing; then place it in a freeze dryer at -80°C and freeze-dry for 24 hours.

[0151] (4) Take a certain amount of the sample in the above step (3) and put it into a crucible, put it into a high-temperature tube furnace in a N2 atmosphere, heat it to 200°C at a heating rate of 8°C / min, keep it at that temperature for 60 minutes, and then cool it naturally to room temperature to obtain a polycrystalline iron-loaded porous biochar aerogel. The biochar aerogel prepared in this embodiment has a single-use catalytic performance similar to that of Example 4, but its reusability is worse than that of Example 4.

[0152] Example 8

[0153] The preparation method of the polycrystalline iron-supported porous biochar aerogel catalyst of this embodiment comprises the following steps:

[0154] (1) Coconut shell carbon was used as the biochar source, nonahydrate and ferric nitrate were used as the iron source, they were mixed and dispersed evenly in ultrapure water, and 10 ml of 1 M nitric acid was added to prevent iron hydrolysis. The mixture was mixed at room temperature for 9 h, the supernatant was removed, and the mixture was dried in an oven overnight. The mixture was then ground through a 100-mesh sieve and calcined in a tubular furnace under the protection of an inert gas. The temperature was raised to 600 °C at a rate of 4 °C / min during the calcination process, and the mixture was kept warm for 2.5 h to obtain a polycrystalline iron biochar material.

[0155] (2) Weigh 1.0 g of polycrystalline iron biochar and 1.2 g of carrageenan as a nitrogen source and binder, put them into a beaker, add 37 ml of deionized water, add 0.8 ml of glacial acetic acid, and then place the beaker on a magnetic stirrer and stir for 50 minutes. After mixing evenly, ultrasonicate for 15 minutes.

[0156] (3) Take 1 ml of the sample in step (2), add it dropwise into a cryopreservation tube, and freeze it in a refrigerator at -15°C until it becomes non-flowing; then place it in a freeze dryer at -70°C and freeze-dry for 24 hours.

[0157] (4) Take a certain amount of the sample in the above step (3) and put it into a crucible, put it into a high-temperature tube furnace in a N2 atmosphere, heat it to 150°C at a heating rate of 5°C / min, keep it warm for 80 minutes, and then cool it naturally to room temperature to obtain polycrystalline iron-loaded porous biochar aerogel. Although the binding ability of coconut shell and iron is weak, due to its high self-generated hardness, it has strong stress resistance and is suitable for engineering conditions. Compared with Example 4, the hardness is higher, but the catalytic performance is slightly reduced.

[0158] Example 9

[0159] The preparation method of the polycrystalline iron-supported porous biochar aerogel catalyst of this embodiment comprises the following steps:

[0160] (1) Straw biochar was used as the biochar source and ferric chloride was used as the iron source. They were mixed and dispersed evenly in ultrapure water, and a certain amount of hydrochloric acid was added to prevent iron hydrolysis. The mixture was mixed at room temperature for 10 h, the supernatant was removed, and the mixture was dried in an oven overnight. The mixture was then ground through a 100-mesh sieve and calcined in a tubular furnace under the protection of an inert gas. The temperature was raised to 400 °C at a rate of 4 °C / min during the calcination process, and the mixture was kept warm for 2.0 h to obtain a polycrystalline iron biochar material.

[0161] (2) Weigh 1.6 g of polycrystalline iron biochar and 1.2 g of sodium alginate as a nitrogen source and binder. Put them into a beaker, add 36.4 ml of deionized water, add 0.8 ml of glacial acetic acid, and then place the beaker on a magnetic stirrer and stir for 60 minutes. After mixing evenly, ultrasonicate for 10 minutes.

[0162] (3) Take 1 ml of the sample in (2), add it dropwise into a cryotube, and place it in a refrigerator at -25°C to freeze it into a non-flowing state; then place it in a freeze dryer at -85°C and freeze-dry it for 20 hours.

[0163] (4) Take a certain amount of the sample in the above step (3) and put it into a customized crucible, put it into a high-temperature tube furnace in a N2 atmosphere, heat it to 130°C at a heating rate of 4°C / min, keep it warm for 90 minutes, and then cool it naturally to room temperature to obtain polycrystalline iron-loaded porous biochar aerogel.

[0164] As agricultural waste, straw has relatively low collection and processing costs. After carbonization, the straw biochar has a small density and small particles. The particle diameter formed after compounding with iron is small, so it can form a fine iron-based biochar catalyst. However, compared with Example 4, its hardness is lower and its performance is slightly worse.

[0165] In summary, the aerogel prepared by the present invention has abundant pores and a large specific surface area. At the same time, the iron-based material and the carbon-based material are cross-linked together by ion exchange of the cross-linking agent. The loading of the polycrystalline iron nanoparticles is relatively firm, which can effectively improve the mechanical strength and structural stability of the catalyst. In addition, the preparation process of the catalyst is simple, the required raw materials are green and pollution-free, the cost is low, and it is easy to mass produce. It can be used in the fields of treating organic pollutants in wastewater and deep purification of drinking water.

Claims

1. A polycrystalline iron-supported porous biochar aerogel catalyst, characterized in that: The internal structure of the catalyst is a honeycomb pore network structure as a whole, which includes a porous biochar matrix, and polycrystalline iron nanoparticles are loaded on the biochar sheet through Fe-C bonds.

2. The porous biochar aerogel catalyst according to claim 1, characterized in that The crystal planes of the polycrystalline iron include but are not limited to the (220) crystal plane of Fe3O4, the (002) crystal plane of Fe3C, the (211) crystal plane of Fe3C, and the (031) crystal plane of Fe2O3.

3. The porous biochar aerogel catalyst according to claim 2, characterized in that: Different crystals of the polycrystalline iron grow alternately inside the biochar layer, and interlaced lattice fringes can be observed under a transmission electron microscope; and / or the loading amount of the polycrystalline iron nanoparticles is 5 to 15% of the mass of the catalyst; And / or the content of the polycrystalline iron accounts for 0.27at% to 37at% of the total amount of the catalyst, wherein Fe(III) accounts for 38at% to 54at% of the total iron content, Fe(II) accounts for 17at% to 31at% of the total iron content, and Fe3C accounts for 17at% to 31at% of the total iron content.

4. The porous biochar aerogel catalyst according to any one of claims 1 to 3, characterized in that The size of the polycrystalline iron nanoparticles is 1 to 10 nm; and / or the diameter of the pores on the biochar matrix is ​​50 to 100 microns.

5. The porous biochar aerogel catalyst according to any one of claims 1 to 3, characterized in that The contact angle of the biochar aerogel is less than 88°; and / or the impedance value of the biochar aerogel is below 11Ω; And / or the ID / IG value in the Raman spectrum of the biochar aerogel is greater than 0.85, and the in-situ Raman spectrum of the biochar aerogel after contacting with O3 in water is 877.74cm -1 、935.76cm -1 and 1004.97cm -1 New peaks appear everywhere.

6. A method for preparing a porous biochar aerogel catalyst according to any one of claims 1 to 5, characterized in that: include: contacting / mixing an iron-based biochar with a cross-linking agent in an aqueous solution to form an iron-based biochar-cross-linking agent mixture; wherein the iron-based biochar comprises a biochar matrix and polycrystalline iron nanoparticles supported on a biochar sheet; The iron-based biochar-crosslinking agent mixture is freeze-dried to form honeycomb-shaped pores in the biochar sheet to obtain the iron-based biochar aerogel; The iron-based biochar aerogel is calcined under an inert atmosphere so that the polycrystalline iron nanoparticles are loaded on the biochar sheet through Fe-C bonds, thereby obtaining the polycrystalline iron-loaded porous biochar aerogel catalyst.

7. The method for preparing the porous biochar aerogel catalyst according to claim 6, characterized in that: The specific surface area of ​​the iron-based biochar is 150 to 250 m 2 / g; and / or the cross-linking agent includes but is not limited to chitosan, carrageenan, sodium alginate, and the mass ratio of the iron-based biochar to the cross-linking agent is (2-5): (1-5); and / or the biochar includes but is not limited to bamboo charcoal, straw biochar, coconut shell charcoal; and / or an organic acid or an inorganic acid is added to the aqueous solution, and the ratio of the iron-based biochar, the cross-linking agent, the organic acid or the inorganic acid, and the water is (0.8g-2g):(0.8g-2g):(0.4ml-0.8ml):(38ml-35.2ml); And / or the freeze-drying treatment of the iron-based biochar-crosslinking agent mixture comprises: first freezing the iron-based biochar-crosslinking agent mixture at -15 to -25°C, and then freeze-drying it at -70 to -85°C; And / or calcining the iron-based biochar aerogel under an inert atmosphere, comprising: heating the iron-based biochar aerogel to 100° C. to 200° C. at a rate of 1 to 8° C. / min, keeping the temperature for 1.0 to 2.0 hours, and then cooling to room temperature.

8. The method for preparing the porous biochar aerogel catalyst according to claim 6 or 7, characterized in that: The iron-based biochar is prepared by a chemical deposition method or a mechanical ball milling method.

9. Use of the porous biochar aerogel catalyst according to any one of claims 1 to 5 in water or air purification systems or chemical catalysis.

10. The use according to claim 9, characterized in that The water purification system includes an ozone catalytic oxidation system, and its use method includes: In the ozone catalytic oxidation system, the porous biochar aerogel catalyst is brought into contact with ozone in the water to be treated to form surface atomic oxygen, which catalyzes the decomposition of ozone to produce singlet oxygen and hydroxyl radicals, thereby enhancing the degradation of pollutants or antibiotics in the water.

Citation Information

Patent Citations

  • A high-elasticity, high-temperature-resistant aerogel and a preparation method thereof

    CN113750917B

  • Chitosan-based biochar with porous structure and high specific surface area as well as preparation method and application of chitosan-based biochar

    CN115634679A